Itinerary books (itineraria) of the Vysotskys’ printing house - N. P. Dvortsova (Библиосфера, 2020)
The study gives a new outlook on the activities of the first Tyumen printing house, which was founded by K. N. Vysotsky in 1869 and existed until 1909. The scientific novelty of the research is due to the following: 1) book publishing is considered as part of the media revolution carried out by K. N. Vysotsky thanks to the opening of the first photography studio (1866), lithography studio (1867), printing house (1869), and a newspaper publishing news and advertisements (1879) in a provincial Siberian town; 2) publishing activities of K. N. Vysotsky and L. K. Vysotskaya are linked with the history of Siberian steam navigation in the 1870–1890s. The purpose of the article is to characterize Russian dorozhniki - itinerary books as a special type of publications in the Vysotskys’ printing house, to identify their diversity and role in the activities of steamship companies, in particular the Kurbatov and Ignatov Partnership. A bibliological analysis based on the structural-typological method within the context and system approaches allows a new interpretation of the role and place of the Vysotskys’ printing house in the history of Siberian book culture. The author comes to the conclusions that about 20% of the repertoire (11 of 56 books) of the Vysotskys’ printing house are books about steamboats and rivers. They represent a semantic unity, a unique series structured by space (more than 3000 km along West Siberian rivers from Tyumen to Tomsk) and the idea of industrialization and cultural development of new lands. The structural dominance of the series belongs to a special publication type: dorozhnik (an itinerary book), the purpose of which was to indicate the distance between settlements and to serve as a travel guide on Siberian rivers. Publication of such books, which are known to exist since the ancient Rome, testifies to the high print culture of the Vysotskys publishers. These books are very diverse: brief guidebooks coexisted with lithographic cartographic editions and advertising catalogs in the genre of history writing and ethnographic travel essays. The significance of the itinerary books published by the Vysotskys lies in the cultural brand they formed for Tyumen as a town and the birthplace of all navigation along West Siberian rivers.